2006
DOI: 10.1111/j.1525-1470.2006.00277.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Atopic Eczema: The Impact of an Educational Intervention

Abstract: Patient education has been regarded as having a key role in the self-management of atopic eczema. However, the relationship between the educational interventions and clinical outcomes including severity of eczema, quality of life, and family impact has not been rigorously examined. The purpose of this longitudinal randomized controlled study was to evaluate the impact of an intensive education program with a focus on dermatology and immunology designed for parents and children diagnosed with atopic eczema. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
204
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(210 citation statements)
references
References 18 publications
(29 reference statements)
0
204
1
5
Order By: Relevance
“…There was a reduction in quality-of-life scores (better quality of life) in the education programme groups compared with the control groups in three [351][352][353] of the six trials. In the trial by Grillo and colleagues 353 the CDLQI at 12 weeks reduced by 7.35 points in the intervention group (education session in addition to normal care) and 2.61 points in the control group (normal care only) (p = 0.004).…”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…There was a reduction in quality-of-life scores (better quality of life) in the education programme groups compared with the control groups in three [351][352][353] of the six trials. In the trial by Grillo and colleagues 353 the CDLQI at 12 weeks reduced by 7.35 points in the intervention group (education session in addition to normal care) and 2.61 points in the control group (normal care only) (p = 0.004).…”
Section: Quality Of Lifementioning
confidence: 99%
“…The trial reported by Grillo and colleagues 353 involved 61 children with eczema and their parents. The trial compared a 2-hour group education session in addition to normal care with normal care alone.…”
Section: Non-pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A therapeutic intervention, i.e. providing parents with more information on atopic dermatitis-related disorders and skin care methods (Therapeutic Patient Education -TPE), results in an increase in adherence, decrease of SCORAD, better quality of life [36][37][38][39] and higher satisfaction with treatment [12]. Improved doctor-parent interaction increases adherence, effectiveness of the therapy and treatment satisfaction of AD [21,40].…”
Section: Analiza Zależności Pomiędzy Przestrzeganiem Zaleceń a Satysfmentioning
confidence: 99%
“…Supporting parents in dealing with the management of AD presents a challenge for physicians 1 . Educational programs for parents and patients with AD have been established in the last ten years in different European countries [3][4][5][6] . Standardized interdisciplinary programs involving dermatologists, pediatricians, psychologists and dietitians improve symptoms and clinical manifestations of AD by optimizing the use of medications resulting in better compliance and leading to a significant increase in the quality of life (QoL) 7 .…”
Section: Introductionmentioning
confidence: 99%